The Effect of Service and Location on Customer Satisfaction at the Andespar Manna Store, South Bengkulu - Eensi Nurye Friza; Sulisti Afriani; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine the effect of service and location on customer satisfaction at the Andespar Manna Bengkulu Selatan Shop. The sampling technique is accidental sampling technique. The data was collected using a questionnaire and the analytical methods used were multiple linear regression, determination test and hypothesis testing. Multiple regression results show the equation Y = 10.878 + 0.444X1 + 0.364 X2+3.784 The resulting regression direction is positive, meaning that the more service and location variables increase, the customer satisfaction will also increase. The coefficient of determination value is 0.852. This means that X1 (service) and X2 (location) have a contribution to customer satisfaction (Y) of 85.2%, while the remaining 14.8% is influenced by other variables not examined in this study. Overall, the results of the t-test have a significant value less than 0.05, so it can be interpreted that X1 (service) and X2 (location) have a significant influence on customer satisfaction (Y) partially or individually. The results of the F test have a significance value of 0.000 <0.05. Because the significance level below 0.05 indicates that together X1 (service) and X2 (location) have a significant effect on customer satisfaction (Y).